Investigation of the interaction between indigotin and two serum albumins by spectroscopic approaches - Zheng-Jun Cheng; Hong-Mei Zhao; Qian-Yong Xu; Rong Liu (Elsevier, 2013)
The binding characteristics of indigotin with human serum albumin (HSA) and bovine serum albumin (BSA) have been investigated by various spectroscopic techniques. Spectroscopic analysis revealed that the quenching mechanism between indigotin and HSA/BSA belonged to the static quenching. The displacement experiments suggested that indigotin primarily bound to tryptophan residues on proteins within site I. The thermodynamic parameters indicated that the binding of indigotinâHSA/BSA mainly depended on the hydrophobic interaction. The binding distance of indigotin to HSA/BSA was evaluated. The results by synchronous fluorescence, three-dimensional fluorescence, Fourier Transform Infrared spectroscopy (FT-IR) and circular dichroism (CD) spectra showed that the conformation of proteins altered in the presence of indigotin. Keywords: Human serum albumin, Bovine serum albumin, Indigotin, Fluorescence spectroscopy, Binding constants